Glucose-inhibition of glucagon secretion involves activation of GABAA-receptor chloride channels. - Rorsman, P; Berggren, P; Bokvist, K; Ericson, H; Möhler, H; Ostenson, C; Smith, P (1989)
The endocrine part of the pancreas plays a central role in blood-glucose regulation. It is well established that an elevation of glucose concentration reduces secretion of the hyperglycaemia-associated hormone glucagon from pancreatic alpha 2 cells. The mechanisms involved, however, remain unknown. Electrophysiological studies have demonstrated that alpha 2 cells generate Ca2+-dependent action potentials. The frequency of these action potentials, which increases under conditions that stimulate glucagon release, is not affected by glucose or insulin. The inhibitory neurotransmitter gamma-aminobutyric acid (GABA) is present in the endocrine part of the pancreas at concentrations comparable to those encountered in the central nervous system, and co-localizes with insulin in pancreatic beta cells. We now describe a mechanism whereby GABA, co-secreted with insulin from beta cells, may mediate part of the inhibitory action of glucose on glucagon secretion by activating GABAA-receptor Cl- channels in alpha 2 cells. These observations provide a model for feedback regulation of glucagon release, which may be of significance for the understanding of the hypersecretion of glucagon frequently associated with diabetes.